2018
DOI: 10.24156/jikk.2017.10.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Parental Self-Efficacy Dan Praktik Pengasuhan Menentukan Perilaku Agresif Anak Usia Prasekolah

Abstract: AbstrakPenelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi perilaku agresif pada anak usia prasekolah. Penelitian ini melibatkan 36 keluarga dengan anak usia prasekolah yang dipilih secara purposive. Kriteria contoh pada penelitian ini adalah ibu sebagai pengasuh utama dan memiliki anak bersekolah di dua lembaga PAUD yang berlokasi di Desa Ciasmara, Kecamatan Pamijahan, Kabupaten Bogor. Data dikumpulkan dengan teknik wawancara menggunakan kuesioner. Data dianalisis menggunakan uji regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
0
4
0
4
Order By: Relevance
“…For example, a study by Hariyani et al (2013) involving 30 parents of children at a kindergarten in Pontianak revealed no significant relationships between parenting styles (rejection, overprotective, acceptance, and permissive parenting) and children's aggression (disturbing playmates, cursing, and bullying). On the contrary, a study by Rachmawati and Hastuti (2017) among 36 parents of young children in Ciasmara village, Bogor, showed that the significant predictors for children's aggressive behaviors (i.e., showing anger, using harsh words, and performing physical attacks) were negatively correlated with parenting practices characterized by strict discipline, anger, and inconsistent parenting. Another study by Zakiyah (2017) with 41 parents of children aged 1-3 years in Pelem, Bantul, indicated significant positive correlations between parenting styles and children's temper tantrums.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, a study by Hariyani et al (2013) involving 30 parents of children at a kindergarten in Pontianak revealed no significant relationships between parenting styles (rejection, overprotective, acceptance, and permissive parenting) and children's aggression (disturbing playmates, cursing, and bullying). On the contrary, a study by Rachmawati and Hastuti (2017) among 36 parents of young children in Ciasmara village, Bogor, showed that the significant predictors for children's aggressive behaviors (i.e., showing anger, using harsh words, and performing physical attacks) were negatively correlated with parenting practices characterized by strict discipline, anger, and inconsistent parenting. Another study by Zakiyah (2017) with 41 parents of children aged 1-3 years in Pelem, Bantul, indicated significant positive correlations between parenting styles and children's temper tantrums.…”
Section: Introductionmentioning
confidence: 96%
“…It appears that studies of parenting and problem behaviors in early childhood, particularly in Indonesia, are still limited, and they did not consistently show significant results. In general, the existing research focuses only on a certain form of problem behaviors such as aggression (Hariyani, Marmawi, & Sutarmanto, 2013;Rachmawati & Hastuti, 2017) and temper tantrums (Watiningsih, Rismayanti, & Sriastiyani, 2018;Zakiyah, 2017). For example, a study by Hariyani et al (2013) involving 30 parents of children at a kindergarten in Pontianak revealed no significant relationships between parenting styles (rejection, overprotective, acceptance, and permissive parenting) and children's aggression (disturbing playmates, cursing, and bullying).…”
Section: Introductionmentioning
confidence: 99%
“…pada pengasuhan, rasa kompeten pengasuhan yang tinggi ditemukan memprediksi praktik pengasuhan yang positif (Dumka et al, 2010), juga dapat membantu orang tua untuk menikmati peran sebagai orang tua dan dapat meningkatkan keterlibatan dalam pengasuhan melalui perilaku suportif yang lebih intens dan efektif dalam penerapan disiplin dan pemantauan (Shumow & Lomax, 2002;Slagt et al, 2012). Sebaliknya, rasa kompeten yang rendah ditemukan berpengaruh terhadap praktik pengasuhan yang negatif (Rachmawati & Hastuti, 2017).…”
Section: Pembahasanunclassified
“…Berbeda halnya ketika anak menerima pengasuhan orang tua yang negatif berupa pengabaian, penolakan, dan lingkungan rumah yang kurang mendukung dalam menstimulasi berdampak pada kurang optimalnya pertumbuhan dan perkembangan anak (Dewanggi, Hastuti, & Hernawati, 2012;Rachmawati & Hastuti, 2017). Hal ini mengindikasikan bahwa perubahan struktur dalam keluarga akan berdampak pada kurang optimalnya peran pengasuhan orang tua yang diberikan pada anak.…”
Section: Berdasarkanunclassified